Ovladavanje jezikom: izvornojezična i inojezična istraživanja - Jelaska, Zrinka (Array, 2007)
The paper discusses names for fields of language development research, eg. the research in language acquisition / learning /development concerning the first / mother language and second / foreign language. As pairs or groups of these terms are synonimes in some cases and different terms in other cases, the meaning relationship between them gets even more complicated when Croatian terminology is included. One reason for this is the fact that the fields of L1 and L2 acqisition, as well as teaching and learning languages are developing very fast and include various types of researchers: linguists, psycholinguists, sociolinguists, psychologists, pedagogists, didactics, cognitive scientists, etc. Not all of them work interdisciplinary, for example: psycholinguists who deal with L2 development do not need to consider the difference between second and foreign language, which is of greatest concern of psycholinguists who deal with motivation, teaching and learning (such as the influence of focus on form on language acqusition) and sociolinguists who deal with attitude towards different languages, as well as their status. As one reason for multiplication of terms is polisemy characteristic for some terms, Croatian terms tend to distinguish hyponimes from hypernym. Therefore terms for aquisition (Cro. usvajanje) and learning (Cro. učenje) get hypernym ovladavanje (Eng. to cover them both - when it is not important of easy to distinguish one from the other, or when both are included. Terms for second (Cro. drugi) and foreign (Cro. strani) get hyperynim ini to cover them both.